2022
DOI: 10.21468/scipostphys.13.5.118
|View full text |Cite
|
Sign up to set email alerts
|

Blast from the past II: Constraints on heavy neutral leptons from the BEBC WA66 beam dump experiment

Abstract: We revisit the search for heavy neutral leptons with the Big European Bubble Chamber in the 1982 proton beam dump experiment at CERN, focussing on those heavier than the kaon and mixing only with the tau neutrino, as these are far less constrained than their counterparts with smaller mass or other mixings. Recasting the previous search in terms of this model and including additional production and decay channels yields the strongest bounds to date, up to the tau mass. This applies also to our updated bounds on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In 2021 the ArgoNeuT experiment 24 also published limits in this region, the BABAR result improves on those limits. In a recent publication Barouki et al 25 showed even tighter bounds. In addition, a recent recasting of the CHARM data, which utilizes data from the electron and muon searches to indirectly constrain the tau sector, has also improved constraints in the same region 26 .…”
Section: Search For Heavy Neutral Leptonsmentioning
confidence: 98%
“…In 2021 the ArgoNeuT experiment 24 also published limits in this region, the BABAR result improves on those limits. In a recent publication Barouki et al 25 showed even tighter bounds. In addition, a recent recasting of the CHARM data, which utilizes data from the electron and muon searches to indirectly constrain the tau sector, has also improved constraints in the same region 26 .…”
Section: Search For Heavy Neutral Leptonsmentioning
confidence: 98%
“…The dashed seesaw line is given by |U α | 2 = ∆m 2 atm /m N corresponding to the naive seesaw scaling and should be considered only as indicative. [1432] and BEBC (recasted) [1764]; ArgoNeut [1781]; BaBar [1612]; DELPHI [1788]; T2K [1786] Coloured curves are projections from: HIKE-dump [1392], SHiP [1402], DarkQuest [1257], Belle II [1782], DUNE [1172], FASER2 [1416]; CODEX-b [1030], and MATHUSLA200 [1441]. The BBN bounds are from [1686].…”
Section: Conclusion On Hnlsmentioning
confidence: 99%
“…Such models have open parameter space where the heavy neutral leptons (HNL) mix only with a single flavour of active neutrinos [1763]. We have carried out work studying the currently least constrained possibility of mixing between HNLs and the tau neutrino [1764]. In this simple model, an HNL N has a mass m N and mixes with the ν τ with a strength given by U τ N .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gray shaded regions are the leading existing constraints from PIENU [78,79], PS191 [13, (although these constraints have recently been reanalyzed and found to be weaker; see [80] for more details), NA62 [81], CHARM [82], BEBC [83,84], Belle [43], DEL-PHI [85], and ATLAS [86] for electron-mixed HNLs; E949 [87], PS191 [13,14], T2K [16,17], NuTeV [88], CHARM [89], Belle [43], DELPHI [85], and ATLAS [86] for muon-mixed HNLS; and NOMAD [15], CHARM [12,15,90], BEBC [84], ArgoNeuT [20], and DELPHI [85] for τ -mixed HNLs. The shaded blue regions at small mixing angles are additional constraints from Big Bang nucleosynthesis (BBN) studies [91,92].…”
Section: Sensitivity Of Lepton Collider Beam Dump Experimentsmentioning
confidence: 99%